Re-wound: Echo's (dis)temporality. Issue 1 (1st January 2021) - Tanti, Emanuel; Rutter Giappone, Krista Bonello
This article considers the displacement suggested by the film's title and the pursuit of the past in the unsettled present. The film occupies an intermediary time and space, as implied by the uncomprehending reactions of those left behind, the investigative reconstruction and the delayed breakthrough of trauma.